Metaphor in Literature: A Study on the Use of Figurative Language in Classical and Modern Works - Faizah, Naela Mikyalul (Journal of Linguistica, 2024)
Metaphors do not only function as linguistic decorations, but also reflect the author's cultural values, social norms, and worldview in the historical context. Classical works, such as poetry and prose by prominent authors, provide deep insight into the traditions, beliefs, and values of the society of the time. The analysis of metaphors allows us to understand how figurative language reflects the spirit of the times that underlies people's thinking. The growing interest in how language creates meaning in a variety of contexts is driving this research. However, there are shortcomings in the research that show a lack of exploration regarding the comparative use of metaphors between classical and modern works. Modern works are also a major focus, where contemporary writers often explore metaphors in innovative ways, creating new meanings that reflect the challenges and dynamics of today's life. In many modern novels, metaphors are used to raise social and political issues, intertwining with the reader's experience. Despite the differences in context and style between classical and modern works, the function of metaphor as a bridge between reality and imagination remains constant. This research is expected to enrich the understanding of the relationship between language, literature, and human experience. In conclusion, despite variations in context and application, metaphors remain an important tool in shaping human understanding of reality and imagination, and have a significant influence on our interactions with the world around us.